2014
DOI: 10.4103/0972-5229.140146
|View full text |Cite
|
Sign up to set email alerts
|

Current practices of mobilization, analgesia, relaxants and sedation in Indian ICUs: A survey conducted by the Indian Society of Critical Care Medicine

Abstract: Background and Aim:Use of sedation, analgesia and neuromuscular blocking agents is widely practiced in Intensive Care Units (ICUs). Our aim is to study the current practice patterns related to mobilization, analgesia, relaxants and sedation (MARS) to help in standardizing best practices in these areas in the ICU.Materials and Methods:A web-based nationwide survey involving physicians of the Indian Society of Critical Care Medicine (ISCCM) and the Indian Society of Anesthesiologists (ISA) was carried out. A que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 58 publications
1
19
2
2
Order By: Relevance
“…(29)Our findings regarding use of SATs and SBTs in Europe (47% and 50%) are also consistent with previously reported data. (27)…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…(29)Our findings regarding use of SATs and SBTs in Europe (47% and 50%) are also consistent with previously reported data. (27)…”
Section: Discussionsupporting
confidence: 93%
“…Nearly all (95%) respondents reported using midazolam for sedation, followed by propofol (68%), and dexmedetomidine (60%); fentanyl was the most common analgesic agent used (47 %). (29)In our study, 35% of respondents reported they do not use sedation protocols, especially those in Africa, Europe and Oceania.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Given the wide variety in practices of early mobilisation around Australia and the world (Chawla et al, 2014, Malone et al, 2015, Nydahl et al, 2014, it is probably prudent to limit extrapolations of these findings to units with similar practices regarding mobilisation and rehabilitation.…”
Section: Strengths and Limitations Of The Studiesmentioning
confidence: 99%